The novel bondless wheel, spherical glass chips and a new method of aspheric generation - Venkatesh, V. C.; Izman, S.; Vichare, P. S.; Mon, T. T.; Murugan, S. (Elsevier B.V., 2005)

(untitled)
Polished partial ductile mode ground surfaces that are the result of relatively low cost processes for ophthalmic, infra-red, and laser optics applications are discussed here. Surfaces obtained during generation of aspheric profiles on glass, Si and Ge have shown formation of massive ductile streaks, which reduce polishing time. A novel imaging technique has been developed to assess the quantity of ductile streaks formed during grinding. Yet another observation is the occurrence of spherical shaped glass chips, which appears to indicate the best cutting conditions. The development of a bondless diamond grinding wheel has resulted in surfaces where the quantity of ductile mode streaks is increased. Finally, a model for arriving at the optimum depth of cut is outlined